ПОДХОДЫ К РАЗРАБОТКЕ СИСТЕМЫ ПОКАЗАТЕЛЕЙ ДЛЯ ХАРАКТЕРИСТИКИ ЭЛЕКТРОННЫХ БИБЛИОТЕК (Библиосфера, 2011)
The relevance of developing a system of indicators to characterize and describe electron libraries created in traditional research libraries is proved. A set of important indicators meeting these goals is proposed. It is shown that this system of indicators is needed both for conduction of a comparative analysis of electronic libraries, and as a certain criterion to distinguish between a set of electronic resources and electronic libraries.